DNA extraction and polymerase chain reaction - Nalini Gupta (Journal of Cytology, 2019)
DNA extraction and polymerase chain reaction (PCR) are the basic techniques employed in the molecular laboratory. This short overview covers various physical and chemical methods used for DNA extraction so as to obtain a good-quality DNA in sufficient quantity. DNA can be amplified with the help of PCR. The basic principle and different variants of PCR are discussed.